Temptation in consumption and optimal redistributive taxation - Maria Arvanitia; Tomas Sjögren (ETH Zurich, CER-ETH - Center of Economic Research, 2020)
The purpose of this article is to integrate the class of preferences developed by Gul and Pesendorfer into the theory of optimal redistributive taxation with heterogenous consumers and asymmetric information. The consumers are inclined to over-spend on a commodity for which they experience temptation (TP good). Resisting that temptation gives rise to a utility cost. This cost provides two novel motives for influencing the consumption and labor supply choices; improving the welfare (by reducing the utility cost of exercising self-control) and providing the government with a novel channel via which tax policy can be used to relax a binding self-selection constraint. The welfare motive implies a positive tax on the TP good, as well as a positive (negative) marginal labor income tax rate if the consumer's marginal valuation of leisure exceeds (falls short of) the marginal valuation of leisure that arises if the consumer would succumb to the temptation. We use iso-elastic and logarithmic utility functional form specifications to exemplify when the self-selection channel may lead to higher/lower commodity and marginal labor income taxes.
Keywords: D03; H21; H24; H31; 330; temptation; self-control; optimal taxation; redistribution; commodity taxation; income taxation